Baseline matters: Challenges and implications of different marine heatwave baselines - Kathryn E. Smith; Alex Sen Gupta; Dillon Amaya; Jessica A. Benthuysen; Michael T. Burrows; Antonietta Capotondi; Karen Filbee-Dexter; Thomas L. Frölicher; Alistair J. Hobday; Neil J. Holbrook; Neil Malan; Pippa J. Moore; et al. (Progress in Oceanography, 2025)

Herbaceous vegetation responses to experimental fire in savannas and forests depend on biome and climate - Zachary J. Gold; Adam F. A. Pellegrini; Tyler K. Refsland; Romina J. Andrioli; Marlin L. Bowles; Dale G. Brockway; Neil Burrows; Augusto C. Franco; Steve W. Hallgren; Sarah E. Hobbie; William A. Hoffmann; Kevin P. Kirkman; et al. (Ecology Letters, 2023)
Fire–vegetation feedbacks potentially maintain global savanna and forest distributions. Accordingly, vegetation in savanna and forest ecosystems should have differential responses to fire, but fire response data for herbaceous vegetation have yet to be synthesized across biomes. Here, we examined herbaceous vegetation responses to experimental fire at 30 sites spanning four continents. Across a variety of metrics, herbaceous vegetation increased in abundance where fire was applied, with larger responses to fire in wetter and in cooler and/or less seasonal systems. Compared to forests, savannas were associated with a 4.8 (±0.4) times larger difference in herbaceous vegetation abundance for burned versus unburned plots. In particular, grass cover decreased with fire exclusion in savannas, largely via decreases in C 4 grass cover, whereas changes in fire frequency had a relatively weak effect on grass cover in forests. These differential responses underscore the importance of fire for maintaining the vegetation structure of savannas and forests.

Right-way fire in Australia's spinifex deserts: An approach for measuring management success when fire activity varies substantially through space and time - Jaume Ruscalleda-Alvarez; Hannah Cliff; Gareth Catt; Jarrad Holmes; Neil Burrows; Rachel Paltridge; Jeremy Russell-Smith; Andrew Schubert; Peter See; Sarah Legge (Journal of Environmental Management, 2023)

Applying Mendelian randomization to appraise causality in relationships between nutrition and cancer - Kaitlin H. Wade; James Yarmolinsky; Edward Giovannucci; Sarah J. Lewis; Iona Y. Millwood; Marcus R. Munafò; Fleur Meddens; Kimberley Burrows; Joshua A. Bell; Neil M. Davies; Daniela Mariosa; Noora Kanerva; et al. (Cancer Causes & Control, 2022)
Dietary factors are assumed to play an important role in cancer risk, apparent in consensus recommendations for cancer prevention that promote nutritional changes. However, the evidence in this field has been generated predominantly through observational studies, which may result in biased effect estimates because of confounding, exposure misclassification, and reverse causality. With major geographical differences and rapid changes in cancer incidence over time, it is crucial to establish which of the observational associations reflect causality and to identify novel risk factors as these may be modified to prevent the onset of cancer and reduce its progression. Mendelian randomization (MR) uses the special properties of germline genetic variation to strengthen causal inference regarding potentially modifiable exposures and disease risk. MR can be implemented through instrumental variable (IV) analysis and, when robustly performed, is generally less prone to confounding, reverse causation and measurement error than conventional observational methods and has different sources of bias (discussed in detail below). It is increasingly used to facilitate causal inference in epidemiology and provides an opportunity to explore the effects of nutritional exposures on cancer incidence and progression in a cost-effective and timely manner. Here, we introduce the concept of MR and discuss its current application in understanding the impact of nutritional factors (e.g., any measure of diet and nutritional intake, circulating biomarkers, patterns, preference or behaviour) on cancer aetiology and, thus, opportunities for MR to contribute to the development of nutritional recommendations and policies for cancer prevention. We provide applied examples of MR studies examining the role of nutritional factors in cancer to illustrate how this method can be used to help prioritise or deprioritise the evaluation of specific nutritional factors as intervention targets in randomised controlled trials. We describe possible biases when using MR, and methodological developments aimed at investigating and potentially overcoming these biases when present. Lastly, we consider the use of MR in identifying causally relevant nutritional risk factors for various cancers in different regions across the world, given notable geographical differences in some cancers. We also discuss how MR results could be translated into further research and policy. We conclude that findings from MR studies, which corroborate those from other well-conducted studies with different and orthogonal biases, are poised to substantially improve our understanding of nutritional influences on cancer. For such corroboration, there is a requirement for an interdisciplinary and collaborative approach to investigate risk factors for cancer incidence and progression.

UAS and Landsat imagery to determine fuel condition for fire behaviour prediction on spinifex hummock grasslands of arid Australia - Paul Rampant; Katherine Zdunic; Neil Burrows (International Journal of Remote Sensing, 2019)

Projected Marine Heatwaves in the 21st Century and the Potential for Ecological Impact - Eric C. J. Oliver; Michael T. Burrows; Markus G. Donat; Alex Sen Gupta; Lisa V. Alexander; Sarah E. Perkins-Kirkpatrick; Jessica A. Benthuysen; Alistair J. Hobday; Neil J. Holbrook; Pippa J. Moore; Mads S. Thomsen; Thomas Wernberg; et al. (Frontiers in Marine Science, 2019)

Dynamics in the global protected‐area estate since 2004 - Edward Lewis; Brian MacSharry; Diego Juffe‐Bignoli; Nyeema Harris; Georgina Burrows; Naomi Kingston; Neil D. Burgess (Conservation Biology, 2019)
Nations of the world have committed to a number of goals and targets to address global environmental challenges. Protected areas have for centuries been a key strategy in conservation and play a major role in addressing current challenges. The most important tool used to track progress on protected‐area commitments is the World Database on Protected Areas (WDPA). Periodic assessments of the world's protected‐area estate show steady growth over the last 2 decades. However, the current method, which uses the latest version of the WDPA, does not show the true dynamic nature of protected areas over time and does not provide information on sites removed from the WDPA. In reality, this method can only show growth or remain stable. We used GIS tools in an approach to assess protected‐area change over time based on 12 temporally distinct versions of the WDPA that quantify area added and removed from the WDPA annually from 2004 to 2016. Both the narrative of continual growth of protected area and the counter‐narrative of protected area removal were overly simplistic. The former because growth was almost entirely in the marine realm and the latter because some areas removed were reprotected in later years. On average 2.5 million km 2 was added to the WDPA annually and 1.1 million km 2 was removed. Reasons for the inclusion and removal of protected areas in the WDPA database were in part due to data‐quality issues but also to on‐the‐ground changes. To meet the 17% protected‐area component of Aichi Biodiversity Target 11 by 2020, which stood at 14.7% in 2016, either the rate of protected‐area removal must decrease or the rate of protected‐area designation and addition to the WDPA must increase.

Categorizing and Naming Marine Heatwaves - Alistair Hobday; Eric Oliver; Alex Sen Gupta; Jessica Benthuysen; Michael Burrows; Markus Donat; Neil Holbrook; Pippa Moore; Mads Thomsen; Thomas Wernberg; Dan Smale (Oceanography, 2018)

Resistin and NGAL are associated with inflammatory response, endothelial activation and clinical outcomes in sepsis - Stephen P. J. Macdonald; Erika Bosio; Claire Neil; Glenn Arendts; Sally Burrows; Lisa Smart; Simon G. A. Brown; Daniel M. Fatovich (Inflammation Research, 2017)

Fire Regimes and Tree Growth in Low Rainfall Jarrah Forest of South-west Australia - Neil Burrows; Bruce Ward; Alex Robinson (Environmental Management, 2010)